Pengaruh Kompos Ampas Tebu terhadap Pertumbuhan dan Hasil Kacang Panjang pada Tanah Alluvial - Ismawan, Eko; Anggorowati, Dini; Huda, Saiful (Fakultas Pertanian Universitas Tanjungpura, 2023)
This study aims to determine the effect of bagasse compost on growth and yield of beans on alluvial soil. This study uses a randomized block designconsisting of 5 treatment, and repeated 5 times, each replication consisted of 5 samples. Those treatments include, k0 without bagasse compost, k1 = 10 tonnes/ha, equivalent to 4.2 kg/plot, k2 = 20 tonnes/ha, equivalent to 8.4 kg/plot, k3 30 tons/ha, equivalent to 12.6 kg/plot, k4 = 40 tonnes/ha, equivalent to 16.8 kg/plot. Variables observed include green level of leaf (SPAD unit), leaf area (cm2), dry weight of the upper part of the plant (g), root volume (cm3), root dry weight (cm3), The number of pods per plant (fruit), length of pods ( cm) and weight of pods per plant (g). Results showed significant effect on the variable observation pod length and pod weight plant however not real effect on the variable observation root volume, root dryweight, leaf area, leaf chlorophyll, and plant dry weightand number of pods.